2022
DOI: 10.1039/d2ra03601k
|View full text |Cite|
|
Sign up to set email alerts
|

Transition metal oxides as a cathode for indispensable Na-ion batteries

Abstract: Na+ ion intercalated layered metal oxides have tremendous applications as the cathode materials for SIBs owing to their superior electrochemical performance compared to other types of cathode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 203 publications
(158 reference statements)
0
29
0
Order By: Relevance
“…The cathode is the most critical component in SIBs which loses electrons during charging and gains them during discharging. 29 The electrochemical properties and life of the battery depend on the structure of the cathode material. 7 The cathode of a battery is usually prepared by the combination of active material (∼ 95%), conductive carbon (∼1%), binder (∼4%), and solvent.…”
Section: Components Of Sibsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cathode is the most critical component in SIBs which loses electrons during charging and gains them during discharging. 29 The electrochemical properties and life of the battery depend on the structure of the cathode material. 7 The cathode of a battery is usually prepared by the combination of active material (∼ 95%), conductive carbon (∼1%), binder (∼4%), and solvent.…”
Section: Components Of Sibsmentioning
confidence: 99%
“…16,18,82 Figure 8 shows the bar diagram where the comparison between the synthesis process is shown with regards to various parameters like raw material availability, scalability, transition metal uniformity, tap density, and control over the morphology for coprecipitation, sol−gel, and solidstate processes. 29,82 4.2. Coprecipitation Reaction Overview.…”
Section: Synthesis Of Ltmo Cathode Via Coprecipitation Techniquesmentioning
confidence: 99%
“…Previous studies suggested that transition metal doping alters the electronic dimensions, provides structural stability, and tunes the light absorption. [14][15][16][17] In most of the previously reported works on the BV dyebased DSSCs, generally photoanode structures were examined to investigate the device performance and stability. Although many nanostructured photoanodes were investigated it was impossible to significantly enhance the DSSC performance due to the insufficient charge collection efficiency, low photoscattering, and higher interfacial charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that the transition metal doping alters the electronic dimensions, provide structural stability, and tuned the light absorption. [14][15][16][17]…”
mentioning
confidence: 99%
“…), which are abundant in resources and low cost. 1,[6][7][8][9][10] Aqueous zinc ion batteries (ZIBs) are considered to be ideal candidates over lithium-ion batteries due to their low redox potential (−0.763 V vs. standard hydrogen electrode (SHE)), 6,[11][12][13] high theoretical specic capacity (820 mA h g −1 and 5855 mA h cm −3 ), 14,15 non-toxic properties 6 and abundant Zn resources. 7 A typical ZIB generally compose of Zn metal anode, electrolyte, and cathode electrode for accommodating Zn ions.…”
Section: Introductionmentioning
confidence: 99%